Environmental Suitability and Supportability for Seaweed Cultivation Development in Terujung Coastal Area, Labuhan Aji, Sumbawa - Hasdinar Firda; Bambang Widigdo; Zairion; Gatot Yulianto (Jurnal Penelitian Pendidikan IPA, 2025)
Global demand for seaweed continues to increase, encouraging Indonesia as a major producer to optimise cultivation areas in a sustainable manner. The Terujung coastal area, located within Saleh Bay, has long been used as a location for seaweed cultivation, but has not been scientifically evaluated in terms of aquatic suitability and carrying capacity. This study aimed to assess the level of suitability and environmental capacity of the area to support the sustainable cultivation of Eucheuma sp. in a sustainable manner. Analyses were conducted using a Geographic Information System (GIS)-based spatial approach and evaluation of water physico-chemical parameters and other supporting factors. Results showed that of the total area of 459,576 hectares, approximately 22.92% was classified as suitable, 58,09% as conditionally suitable, and 18.99% as unsuitable. The calculation of carrying capacity shows that only 89,35 hectares of area can be optimally utilized, with a maximum capacity of 178 longline units. This study provides a scientific basis for aquaculture zoning planning based on environmental suitability in the Terujung Coastal water.